The COVID lockdown and its effects on soft tissue injuries in Premier League Athletes - Mannino, B. J.; Yedikian, T.; Mojica, E. S.; Bi, A.; Alaia, M.; Gonzalez-Lomas, G. (The Physician and Sportsmedicine, 2023)
Background: During the COVID impacted 2020-2021 season of the English soccer league, there was an appreciable number of injuries experienced by players. These injuries, however, have not been quantified against previous seasons to highlight the altered season as a causative factor. Methods: A review of an online database was conducted to search for injuries to football players in the Premier League across three seasons; 2018-2019, 2019-2020, and 2020-2021, to compare for difference in injury rates across the years and assess for higher rates in this current season, where athletes have had less play time due to COVID-19. Injury number and injury characteristics were abstracted from the online database Transfermarkt, with the provided information allowing for the sorting of the data into muscular and ligamentous injuries and skeletal injuries. Results: Overall 226, 260, and 289 muscular and ligamentous injuries were observed across the 2018/2019, 2019/2020, and 2020/2021 seasons, respectively. There were 495 minutes on average played leading up to first injury in the 2020/2021 season, compared with 521 minutes in the 2019/2020 season and 536 minutes in the 2018/2019. There was an average of games played to injury of 5.6 games in the 2020/2021 year, with 6.0 in the 2019/2020 year and 6.1 in the 2018/2019 year. Additionally, there was a significantly shorter time in between games was noted during the COVID-affected season with a mean time of 6.8 days in-between games played during the 2020-2021 season as compared to the previous years of 9.12 and 7.12 days. Conclusion: Our study found that there were more injuries and a decreased time to first injury observed during the COVID-impacted 2020-2021 season than the two preceding seasons, perhaps demonstrating a link between fixture congestion and athlete injuries as evidenced by the significantly shorter time between games. It is therefore prudent to retain fixture spacing for athlete recovery even against the backdrop of an overall shortened season.